Relating substitution to single-chain conformation and aggregation in poly(p-phenylene vinylene) films - Kemerink, Martijn; Duren, Jeroen Karolus Johannes van; Jonkheijm, Pascal; Pasveer, W. Frank; Koenraad, Paulus M.; Janssen, René A. J.; Salemink, Huub W.; Wolter, Joachim H. (Nano letters, 2003)
The morphology of films of PPV derivatives is studied with molecular (single chain) resolution by phase-imaging scanning force microscopy. It is found that the symmetry of substitution is directly related to surface morphology and aggregation behavior. The molecular resolution in the phase contrast is shown to result from van der Waals interaction between the conjugated backbone of the polymer chains and the metallic tip, and can quantitatively be described by a simple harmonic oscillator model.
Gesehen am 16.12.2019